Mesenchymal stromal/stem cells as potential therapy in diabetic retinopathy. - Fiori, Agnese; Terlizzi, Vincenzo; Kremer, Heiner; Gebauer, Julian; Hammes, Hans-Peter; Harmsen, Martin C; Bieback, Karen (Immunobiology, 2018)
Europe PMC is an archive of life sciences journal literature., Mesenchymal stromal/stem cells as potential therapy in diabetic retinopathy.